Multi-spectral investigation of ozone: Part II. Line intensity measurements at one percent accuracy around 5 µm and 10 µm. (March 2022) - Jacquemart, David; Boursier, Corinne; Elandaloussi, Hadj; Jeseck, Pascal; Té, Yao; Janssen, Christof
Highligths: Accurate measurements of ozone line positions and intensities at 10 µ m and 5 µ m. Detailed comparison of new results with databases and literature values. Systematic biases at 10 µ m and at 5 µ m are revealed in current versions of databases. Abstract: Ozone line parameters have been retrieved from high-resolution Fourier transform spectra in the 5- µ m and 10- µ m spectral regions using a H-shaped cell with two parallel paths described in the first paper of the series (Multi-spectral investigation of ozone: Part I. Setup & uncertainty budget). The experimental arrangement allows for quasi simultaneous acquisition of spectra at 5 µ m and 10 µ m with consistent ozone pressure. A multispectrum fitting procedure has been used to accurately measure line positions and intensities. Special care has been taken to determine the instrument line shape and its effect on line intensities and sources of uncertainties from the assumption of a molecular line profile have been investigated. Line positions and intensities have been retrieved for 497 transitions at 10 µ m, mostly (476) from the ν3 band, but also from the ν1 band (18 transitions) and from the ν2 +ν3 –ν2 hot band (3 transitions). At 5 µ m, 319 transitions have been determined, of which 316 belong to the ν1 +ν3 and 3 to the 2ν3 bands. Comparisons with previous experiments and calculations as well as with databases are presented, showing systematic discrepancies. The new intensity data at the unprecedented 1% accuracy level unambiguously indicates that atmospheric databases currently suffer from systematic biases up to 4.2% in the ν1 +ν3 band and 2.2% in the ν3 band. The present results will help to resolve the long-standing UV-IR discrepancy observed in atmospheric and laboratory ozone studies. Comparisons with yet unpublished measurements and Hamiltonian-type calculations, as well as with recently published ab-initio calculations show an average discrepancy between 0.1% and 1.2% with sub-percent (0.4–0.8%) dispersion. The small scatter of the comparison confirms the sub-percent precision of both, the calculations, and the measurements. Graphical abstract: Image, graphical abstract